Determinants of Novice, Portfolio and Serial Entrepreneurship: An Occupational Choice Approach - Hien Thu Tran; Emanuela Carbonara; Enrico Santarelli (Global Labor Organization (GLO), 2017)
In this paper we present an occupational choice model for entrepreneurs, in which, based on their individual skills and on the quality of their business, entrepreneurs can keep their original business, open a new business in the same or another sector along the current business (portfolio entrepreneur), shut it down to either start a new one (serial entrepreneur) or to turn to dependent employment. We test our theory using a 10-year panel dataset (2001 to 2010) of more than 4,000 Vietnamese manufacturing firms. We estimate an occupational choice model and a survival model and find that: (i) a greater endowment of human capital is associated with a higher likelihood to become a serial or a portfolio entrepreneur; (ii) A higher quality of the new business is associated to a higher likelihood of being habitual entrepreneurs. Particularly, high entrepreneurial skills together with a high-quality business positively influence the likelihood to be serial or portfolio; (iii) novice entrepreneurs with high entrepreneurial skill and a high-quality business are more likely to keep their business.
Keywords: F02; L26; L53; 330; Portfolio entrepreneurship; serial entrepreneurship; occupational choice; industrial policy